Determinants Of Internal Vs. External Ceo Successions In Malaysian Public Listed Companies - Ishak, Rokiah; Ku Ismail, Ku Nor Izah; Abdullah, Shamsul Nahar (Asian Academy of Management (AAM), 2012)
Following a CEO turnover, a company may select an internal or external successor. The objective of this study is to determine if firm performance, board attributes, ownership structure and incumbent power influence the decision of whether to elect an internal or external candidate. Results from logistic regression analysis on 145 succession events over a four-year period (2002 to 2005) indicate that firms which are controlled by blockholders tend to select an outsider as the successor. Further, firms that are controlled by family members and position their former CEOs within the firms are more likely to select insiders as successors. However, firm performance, board composition, CEO duality and turnover type do not affect the selection choice. This study implies that poor firm performance does not necessarily lead to outside CEO selection choice. Further, boards of Malaysian PLCs are not effective in choosing outsiders as successors as both board composition and CEO duality do not necessarily select outsiders to become new CEOs. Another implication of this study is that former CEOs who continue their directorship in the same companies do have some power in naming new CEOs as the former tend to select insiders as successors.